Civil Rights in the Texas Borderlands : Dr. Lawrence A. Nixon and Black Activism - Guzmán, Will (University of Illinois Press, 2015)
In 1907, physician Lawrence A. Nixon fled the racial violence of central Texas to settle in the border town of El Paso. There he became a community and civil rights leader. His victories in two Supreme Court decisions paved the way for dismantling all-white political primaries across the South. Will Guzmán delves into Nixon's lifelong struggle against Jim Crow. Linking Nixon's activism to his independence from the white economy, support from the NAACP, and the man's own indefatigable courage, Guzmán also sheds light on Nixon's presence in symbolic and literal borderlands--as an educated professional in a time when few went to college, as an African American who made waves when most feared violent reprisal, and as someone living on the mythical American frontier as well as an international boundary. A powerful addition to the literature on African Americans in the Southwest, Civil Rights in the Texas Borderlands explores seldom-studied corners of the Black past and the civil rights movement.